Pengaruh Temperatur Pemanasan pada Proses Penempaan Pembuatan Katup Gas - Shelo Sujendro; Ratna Dewi Anjani; Aa Santosa (Universitas Muhammadiyah Yogyakarta, 2023)
Manufacturing of valves generally uses brass alloy materials and is carried out using a forging process. In this research, the aim is to determine the effect of variations in heating temperature in the valve manufacturing process on the hardness value, microstructure, and shape changes that occur. This research method uses this research method, using an experimental method with temperature variations tested of (300˚, 400˚, and 500 ˚Celsius) with an unchanged compressive force and brass raw material with specifications Cu = 57%. Results of observations that occurred namely Hardness Testing, the lower the heating temperature, the higher the resulting hardness value, which is 69 HRb, 66 HRb, and 59 HRb. When the shape changes, the higher the temperature, the more flash you get, and the lighter the forging force on the forging tool. In the microstructure, as a result of temperature differences, each grain structure characteristic will be different, increasing temperature and forging pressure will change the grain structure.